A multi‐centre randomized controlled trial of mobile gynaecological cancer support program for patients with gynaecological cancer undergoing chemotherapy: Study protocol. (23rd February 2021) - Lin, Huicong; Chan, Sally Wai‐chi; Ye, Mingzhu; Wang, Yanlong; Liu, Hongli; Li, Min; Liu, Shengjie; Zhu, Jiemin
Abstract: Aim: Patients with gynaecological cancer often experience high levels of uncertainty in illness during chemotherapy and report unmet supportive care needs. Mobile applications (apps) are increasing being used as an easily accessible alternative to support these patients, but a lack of rigorous trials have been conducted to explore their effectiveness. Based on Mishel's uncertainty in illness theory, the Mobile Gynaecological Cancer Support (MGCS) program is an app‐based program that includes four modules: 1) weekly topics, 2) emotional care, 3) discussion centre and 4) health consultation. The aim of this study is to assess the effectiveness of MGCS for Chinese patients with gynaecological cancer receiving chemotherapy in respect of reducing uncertainty in illness and symptom distress and improving quality of life and social support. Design: A multi‐centre randomized controlled trial will be used. Methods: One hundred and sixty‐eight patients with gynaecological cancer commencing chemotherapy will be recruited from three university affiliated hospitals and assigned to the control or intervention group with block randomization. The control group will only receive routine care. The intervention group will access the MGCS program for 24 weeks and receive routine care. Health outcomes will be evaluated at baseline, 12 weeks, and 24 weeks. Repeated measures multivariate analysis of covariance (intention‐to‐treat) will be used to assess the effectiveness of MGCS. Discussion: This is the first trial to explore the effectiveness of an app‐based program for patients with gynaecological cancer using a robust and rigorous study design in China. If effective, this trial will provide evidence for an app‐based program to support these patients. Impact: The knowledge gained can be applied to develop other culturally appropriate app‐based programs for cancer groups worldwide, and provide evidence for health policymakers to allocate more resources and train staff for e‐health. Trial Registration: ChiCTR2000033678 (Chinese Clinical Trial Registry Registered 08 June, 2020).